Morphological features of the globose nucleus of the cerebellum - Shyian D.N. (Морфологія, 2016)
Background. The study of the clinical anatomy and functional features of the cortex, subcortical and conductive pathways of the cerebellum is necessary for clinicians for elaboration of rational surgical approaches to these formations, for determination the localization of pathological processes associated with these formations. In this article morphological features of the globose nucleus of the cerebellum were studied. Objective. The aim of this study is to investigate the morphological features of spherical nuclei of the cerebellum. Methods. The study was conducted at 340 specimens of the cerebellum of people aged from 20 to 99 years old. Macro- and microscopic, morphometric, histologic methods and methods of statistical analysis were used. Results. Individual variability in size of spherical nucleus considering the size of the cerebellar vermis was established. It determines the location of the border relatively to the median sagittal plane, topographic and anatomic particular location in relation to other nuclei of the cerebellum. Variantions of the nucleus were established. Conclusion. We have established dimensions of globose nucleus, its shape and location regarding the median-sagittal plane. The globose nucleus on the sections made in a horizontal plane has a bulk-rounded shape at 65,88% (224 cases). At 34,12% (116 cases) it consists of a cluster of different sizes` nuclei and it does not always correspond to the shape of the ball, since in this case it may be not only round, but also have an elongated oval outline in the longitudinal direction. The plate of its gray matter has small spherical winding cogs in the shape of wavy line. Citation: Shyian DN. Morphological features of the globose nucleus of the cerebellum. Morphologia. 2016;10(1):92-5.